An insight on the future therapeutic application potential of Stevia rebaudiana Bertoni for atherosclerosis and cardiovascular diseases - Ilias, Nazhan; Hamzah, Hazilawati; Ismail, Intan Safinar; Mohd. Mohidin, Taznim Begam; Idris, Mohd. Faiz; Ajat, Mokrish (Elsevier, 2021)
Stevia rebaudiana Bertoni is a native plant to Paraguay. The extracts have been used as a famous sweetening agent, and the bioactive components derived from stevia possess a broad spectrum of therapeutical potential for various illnesses. Among its medicinal benefits are anti-hypertensive, anti-tumorigenic, anti-diabetic, and anti-hyperlipidemia. Statins (3-hydro-3-methylglutaryl-coenzyme A reductase inhibitor) are a class of drugs used to treat atherosclerosis. Statins are explicitly targeting the HMG-CoA reductase, an enzyme in the rate-limiting step of cholesterol biosynthesis. Despite being widely used in regulating plasma cholesterol levels, the adverse effects of the drug are a significant concern among clinicians and patients. Hence, steviol glycosides derived from stevia have been proposed as an alternative in replacing statins. Diterpene glycosides from stevia, such as stevioside and rebaudioside A have been evaluated for their efficacy in alleviating cholesterol levels. These glycosides are a potential candidate in treating and preventing atherosclerosis provoked by circulating lipid retention in the sub-endothelial lining of the artery. The present review is an effort to integrate the pathogenesis of atherosclerosis, involvement of lipid droplets biogenesis and its associated proteins in atherogenesis, current approaches to treat atherosclerosis, and pharmacological potential of stevia in treating the disease.